Analisis Perbandingan Harga Saham Sebelum dan Sesudah Pemboikotan Konsumen Atas Isu Geopolitik Israel Palestina Pada Perusahaan Unilever Indonesia Tbk - Ari Almansyah; Lella Anita; Esty Apridasari; Ani Nurul Imtihanah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The Israeli-Palestinian geopolitical conflict and the Indonesian Ulema Council (MUI) Fatwa No. 83/2023 triggered a boycott that could potentially impact the stock performance of national companies. The purpose of this study is to analyze the difference in stock prices of PT Unilever Indonesia Tbk before and after the consumer boycott. This study applies a comparative descriptive method with an event study approach, using closing price data for the 6-month period before and 6-month period after the boycott was ratified on October 7, 2023, sourced from Investing.com with a total of 242 daily stock price data. Data analysis includes descriptive statistics, the Kolmogorov-Smirnov Test for normality, the Wilcoxon Signed Rank Test for pairwise differences, and the effect size test. The results show a decrease in the average stock price from Rp4,079.17 to Rp3,275.87 and a significant difference between the two periods with a significance value (0.001 ≤ 0.05) and an effect size value of 0.61, indicating a moderate boycott effect. These findings align with the theory of market efficiency, which asserts that stock prices quickly adjust to public information, and with signaling theory, which argues that boycotts are a negative signal to investors. Based on the analysis, the researchers concluded that geopolitical and socio-religious issues can impact stock price stability in the Indonesian capital market and serve as a warning to companies to maintain their image and transparency when addressing sensitive global issues.